Great American Burger Book: How to Make Authentic Regional Hamburgers at Home - George Motz (Harry N. Abrams, 2016)
The Great American Burger Book is the first book to showcase a wide range of regional hamburger styles and cooking methods. Author and burger expert George Motz covers traditional grilling techniques as well as how to smoke, steam, poach, and deep-fry burgers based on signature recipes from around the country. Each chapter is dedicated to a specific regional burger, from the tortilla burger of New Mexico to the classic New York–style pub burger, and from the fried onion burger of Oklahoma to Hawaii’s Loco Moco. Motz provides expert instruction, tantalizing recipes, and vibrant color photography to help you create unique variations on America’s favorite dish in your own home.